Advances in neural networks - ISNN 2005 Second International Symposium on Neural Networks, Chongqing, China, May 30 - June 1, 2005 : proceedings, part I - ISNN 2005 (Simpósio) (Lecture notes in computer science)
The three volume set LNCS 3496/3497/3498 constitutes the refereed proceedings of the Second International Symposium on Neural Networks, ISNN 2005, held in Chongqing, China in May/June 2005. The 483 revised papers presented were carefully reviewed and selected from 1.425 submissions. The papers are organized in topical sections on theoretical analysis, model design, learning methods, optimization methods, kernel methods, component analysis, pattern analysis, systems modeling, signal processing, image processing, financial analysis, control systems, robotic systems, telecommunication networks, incidence detection, fault diagnosis, power systems, biomedical applications, industrial applications, and other applications. Theoretical analysis -- Model design -- Learning methods -- Optimization methods -- Kernel methods -- Component analysis.